Caffeine coingested with carbohydrate on performance recovery in national-level paddlers: a randomized, double-blind, crossover, placebo-controlled trial - Barzegar, H.; Arazi, H.; Mohebbi, H.; Sheykhlouvand, M.; Forbes, S. C. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Caffeine enhances muscle glycogen resynthesis postexercise; however, the next-day effects on recovery are unknown. The present study aimed to examine the effects of carbohydrate (CHO) supplementation with or without caffeine (CAF) 24-h following exhaustive exercise on time trial performance in elite paddling athletes. METHODS: Nine highly trained male paddlers (21±2 y) completed three experimental trials in a randomized, double-blind, crossover manner. Following an exhaustive exercise session (20-km timed paddle) participants ingested: 1) 0.6 g/kg of carbohydrate (CHO); 2) 0.6 g/kg of carbohydrate with 6 mg/kg of caffeine (CAF+CHO); or 3) placebo (PLA), at four time-points (immediately after, and 2, 6, and 12-h postexercise) in addition to their typical dietary intake. After 24 h, 5 attempts of on-water 500-m paddling time-trial was performed, and the average time was recorded. Blood samples were taken at rest and following both the 20-km and the 5×500 m exercise to determine changes in plasma cortisol, insulin, and glucose. RESULTS: There was a significant main effect of condition (P<0.001), with post-hoc analysis revealing that both CHO conditions (CHO: 98.7±2.8 s, P=0.0003; CAF+CHO: 97.9±2.3 s, P=0.0002) were significantly faster compared to PLA (101.0±3.1 s); however, CAF did not augment time trial performance compared to CHO (P=0.16). There was no significant condition by time interactions for glucose, cortisol, or insulin before and after the 20-km depleting exercise and 500-m time trial. CONCLUSIONS: In elite male paddlers, CHO, independent of caffeine, enhanced time trial performance 24 hours following exhaustive exercise.